A Theoric Study About Management and Measurement of Intellectual Capital - ARINazmiye Ülkü (Information Management and Business Review, 2014)
With the winds of global competition, individual and mass improvements that experienced in the transition to the information society caused occurence of many concepts. In the other words, the improvements in the communication and information technologies caused strong fundamental changes by affecting organizations’ structures, functioning and competitiveness. With these changes, new formations occured and intellectual capital are started to be considered. All these improvements and changes connected the future of today’s organizations to intellectual capital which has been known as the capability and power of producing the knowledge and converting it to a source of wealth. In today’s information age, to have the intellectual capital is so important. It became more important with management improvement of it and becoming more visible as it gives an advantage of competition and an increase of market value to the organizations. Fort this purpose, in this study, the concept of intellectual capital and management and measurement of intellectual capital have been defined as a theoretical perspective. The change and development of the point of view to intellectual capital concept has been defined.